A review of the literature on the Belt and Road Initiative with factors influencing the transport and logistics. Issue 4 (19th May 2022) - Chen, Dongxu; Song, Dongping; Yang, Zhongzhen
ABSTRACT: This paper reviews the literature on the Belt and Road Initiative (BRI), which has the factors that directly influence the transport and logistics. The relevant literature has been collected systematically since the BRI was initiated in 2013. We adopt a content analysis methodology involving a four-step process. It can be found that firstly, more and more papers on the BRI have been published these years and the influence of BRI on transport and logistics can be summarized into three main perspectives, namely, the changes of the politics & policy, the changes of the environmental dimensions, the direct influence on transport and logistics; secondly, the topics and adopted methodology have been summarized, and it can be found that the percentage papers using quantitative analysis increases over the years; thirdly, percentage of papers with optimistic attitude on the BRI has been increasing since 2013 and compared with authors with affiliations in China, authors with non-Chinese affiliations are more likely to show pessimistic attitudes; fourthly, the research gaps have been summarized, which illustrates future research direction or topics and can promote the studies on transport and logistics considering the influence of the BRI and provides theoretical basis for BRI's development.